« Projet de formation » : accompagner vers la réussite universitaire et l’insertion professionnelle - Mikaël De Clercq; Véronique Leroy; Florence Stinglhamber; Mariane Frenay (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
Transition and adjustment to the academic life, as well as vocational orientation, are major challenges for university students. In order to address these issues, many support activities are proposed by universities. However, their actual impact on students is overlooked. The aim of this research is to present the results of an evaluation of a, activity, called “projet de formation” which supports both students’ academic adjustment and vocational orientation. This evaluation was carried out with two cohorts of students, three years apart, and according to three levels of analysis that are derived from Kirkpatrick and Kirkpatrick’s assessment model. The results of this study show a significant increase in the perceived benefits of the activity, as well as a reported increase in the transfer of acquired skills. After pointing out the limitations of our study, we discuss perspectives for future research on the evaluative approach that is used.